Cardiovascular-kidney-metabolic syndrome: association with adverse events after major noncardiac surgery - Roth, Sebastian; M’Pembele, René; Matute, Purificación; Kotfis, Katarzyna; Larmann, Jan; Lurati Buse, Giovanna (Anesthesia & analgesia, 2024)
BACKGROUND: - The American Heart Association (AHA) recently defined the cardiovascular-kidney-metabolic syndrome (CKM) as a new entity to address the complex interactions between heart, kidneys, and metabolism. The aim of this study was to assess the outcome impact of CKM syndrome in patients undergoing noncardiac surgery. - METHODS: - This is a secondary analysis of a prospective international cohort study including patients aged ≥45 years with increased cardiovascular risk undergoing noncardiac surgery. Main exposure was CKM syndrome according to the AHA definition. The primary end point was a composite of major adverse cardiovascular events (MACE) 30 days after surgery. Secondary end points included all-cause mortality and non-MACE complications (Clavien-Dindo class ≥3). - RESULTS: - This analysis included 14,634 patients (60.8% male, mean age = 72±8 years). MACE occurred in 308 patients (2.1%), and 335 patients (2.3%) died. MACE incidence by CKM stage was as follows: CKM 0: 5/367 = 1.4% (95% confidence interval [CI], 0.4%-3.2%); CKM 1: 3/367 = 0.8% (95% CI, 0.2%-2.4%); CKM 2: 102/7440 = 1.4% (95% CI, 1.1%-1.7%); CKM 3: 27/953 = 2.8% (95% CI, 1.9%-4.1%); CKM 4a: 164/5357 = 3.1% (95% CI, 2.6%-3.6%); CKM 4b: 7/150 = 4.7% (95% CI, 1.9%-9.4%). In multivariate logistic regression, CKM stage ≥3 was independently associated with MACE, mortality, and non-MACE complications, respectively (MACE: OR 2.26 [95% CI, 1.78-2.87]; mortality: OR 1.42 [95% CI: 1.13 -1.78]; non-MACE complications: OR 1.11 [95% CI: 1.03-1.20]). - CONCLUSION: - The newly defined CKM syndrome is associated with increased morbidity and mortality after non-cardiac surgery. Thus, cardiovascular, renal, and metabolic disorders should be regarded in mutual context in this setting.
Gesehen am 10.10.2024